ZINC TRANSPORTER5 and ZINC TRANSPORTER9 Function Synergistically in Zinc/Cadmium Uptake. Issue 3 (27th April 2020) - Tan, Longtao; Qu, Mengmeng; Zhu, Yuxing; Peng, Can; Wang, Jiurong; Gao, Dongying; Chen, Caiyan
Abstract : Zinc influx transport proteins function synergistically in rice to maintain zinc homeostasis. Abstract: The elements Zinc (Zn) and cadmium (Cd) have similar chemical and physical properties, but contrasting physiological effects in higher organisms. In plants, Zn/Cd transport is mediated by various transporter proteins belonging to different families. In this study, we functionally characterized two Zn transporter genes in rice ( Oryza sativa ), ZINC TRANSPORTER5 ( OsZIP5 ) and ZINC TRANSPORTER9 ( OsZIP9 ), which are tandem duplicates and act synergistically in Zn/Cd uptake. Both genes encode plasma membrane-localized proteins with influx transporter activity. The expression profiles of OsZIP5 and OsZIP9 overlap in the root epidermis and respond to the local Zn status in the root. However, OsZIP9 is also regulated by systemic signals of Zn status from the shoot. OsZIP5 functions redundantly to OsZIP9, but has a relatively weaker effect. Plants with the knockout mutations oszip5, oszip9, or oszip5oszip9 show impaired Zn/Cd uptake. The decreased Zn/Cd levels and growth retardation in the oszip5 mutant are less severe than in the oszip9 mutant. However, the double mutant oszip5oszip9 showed an enhanced Zn deficiency phenotype compared with the single mutants, and few double-knockout plants were able to survive the entire growth cycle without excessive Zn supply. Transgenic plants overexpressing OsZIP9 had markedly enhanced Zn/Cd levels in the aboveground tissues and brown rice. The results of our study fill a gap in current knowledge of Zn uptake and improve our understanding of Zn/Cd accumulation in rice.